Resource curse: A comparative study - Behzad Azarhoushang; Marko Rukavina (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2014)
Weak economic performance of most oil rich countries states that natural resources are more curse than blessing for these countries. Resource curse theory examines the negative effects of rich natural resources on economic growth from an economic and political perspective. Since 1960s appreciation of real domestic exchange rate (Dutch Disease) was explained as the main reason for poor economic performance of oil rich countries. But since 1990s, other causes such as long lasting ineffective institutions, corruption and rent seeking are considered to be other major political reasons behind backwardness of most resource rich countries. These political features are the corner stone of Resource Curse theory. In this paper we examine the viability of Resource Curse theory for Iran, Russia and Norway to see whether natural resources are curse or blessing for these countries. Furthermore, we compare main macroeconomic and good governance indicators from 2000 to 2010 of Iran with Turkey and Russia with China to illustrate the negative effects of oil revenue on economic performance. The result of this research shows that institutional quality has vital role in sustainable economic development. Norway as a successful oil rich country shows that efficient institutions can turn natural resource into blessing; while Iran's and Russia's experiences are a clear example of resource curse.
Keywords: O11; O52; O53; 330; Resource Curse; Dutch Disease; Iran; Russia; Norway; China; Turkey